Characterization of a new lytic bacteriophage vB_RanS_GDF21 and its endolysin LysGDF21 with antimicrobial activity against Riemerella anatipestifer - Zhao, Yaru; Liu, Yulan; Jiang, Yina; Li, Xiaoting; Si, Zhenshu; Lu, Jianbiao; Cao, Shengliang; Xue, Xijuan; Li, Yubao; Liu, Cheng (Frontiers in Microbiology, 2026)
IntroductionRiemerella anatipestifer (R. anatipestifer) presents as a major pathogen causing septicemia among poultry. The complex serotype diversity and multidrug resistance of R. anatipestifer severely compromise infection prevention and treatment strategies. Bacteriophages and their endolysins represent a promising alternative strategy against R. anatipestifer.MethodsThe phage vB_RanS_GDF21 (GDF21) was isolated from feces of a duck farm, and its biological properties were characterized. Whole-genome sequencing was performed using the Illumina NovaSeq 6000 platform, followed by a bioinformatic analysis of the genome. The derived endolysin, LysGDF21 (encoded by orf 65), was expressed in Escherichia coli BL21 (DE3), and its anti-biofilm and antimicrobial activities were assessed.ResultsTransmission electron microscopy showed that phage GDF21 had an icosahedral symmetric head, and a long, non-contractile tail. It exhibited a 20 min eclipse period, burst size of 74 PFU/infected cell, and stability at pH 5-11 and temperatures below 50 °C. Whole-genome sequencing revealed that GDF21 possesses a double-stranded DNA genome with length of 46,925 bp and G+C content of 35.25%. Among the 75 predicted ORFs, 27 were functionally annotated and no genes associated with virulence or antibiotic resistance were identified. Phylogeny and classification analysis indicated that GDF21 is a member of the class Caudoviricetes and is closely related to Riemerella phage vB_RanS_CRP19. LysGDF21 significantly inhibited biofilm formation and disrupted mature biofilms in R. anatipestifer. When combined with EDTA, LysGDF21 exhibited broad antibacterial activity against R. anatipestifer.ConclusionThe characterization of phage GDF21 enriches the phage database, while the potent anti-biofilm and antibacterial activities of LysGDF21 highlight its therapeutic potential against R. anatipestifer infections.